Range-Wide Population Structure of 3 Deepwater Eteline Snappers Across the Indo-Pacific Basin. (17th August 2020) - Andrews, Kimberly R; Copus, Joshua M; Wilcox, Christie; Williams, Ashley J; Newman, Stephen J; Wakefield, Corey B; Bowen, Brian W
Abstract: Deep-sea habitats may drive unique dispersal and demographic patterns for fishes, but population genetic analyses to address these questions have rarely been conducted for fishes in these environments. This study investigates the population structure of 3 tropical deepwater snappers of the genus Etelis that reside at 100–400 m depth, with broad and overlapping distributions in the Indo-Pacific. Previous studies showed little population structure within the Hawaiian Archipelago for 2 of these species: Etelis coruscans and E. carbunculus . Here we extend sampling to the entire geographic range of each species to resolve the population genetic architecture for these 2 species, as well as a recently exposed cryptic species ( Etelis sp .). One goal was to determine whether deepwater snappers are more dispersive than shallow-water fishes. A second goal was to determine whether submesophotic fishes have older, more stable populations than shallow reef denizens that are subject to glacial sea-level fluctuations. Both goals are pertinent to the management of these valuable food fishes. A total of 1153 specimens of E. coruscans from 15 geographic regions were analyzed, along with 1064 specimens of E. carbunculus from 11 regions, and 590 specimens of E. sp. from 16 regions. The first 2 species were analyzed with mtDNA and 9–11 microsatellite loci, while E. sp. was analyzed with mtDNA only. Etelis coruscans had a non-significant microsatellite global FST, but significant global mtDNA Ф ST = 0.010 ( P = 0.0007), with the isolation of Seychelles in the western Indian Ocean, and intermittent signals of isolation for the Hawaiian Archipelago. Etelis carbunculus had a non-significant microsatellite global FST, and significant global mtDNA Ф ST = 0.021 ( P = 0.0001), with low but significant levels of isolation for Hawaiʻi, and divergence between Tonga and Fiji. Etelis sp. had mtDNA Ф ST = 0.018 ( P = 0.0005), with a strong pattern of isolation for both Seychelles and Tonga. Overall, we observed low population structure, shallow mtDNA coalescence (similar to near-shore species), and isolation at the fringes of the Indo-Pacific basin in Hawaiʻi and the western Indian Ocean. While most shallow-water species have population structure on the scale of biogeographic provinces, deepwater snapper populations are structured on the wider scale of ocean basins, more similar to pelagic fishes than to shallow-water species. This population structure indicates the capacity for widespread dispersal throughout the Indo-Pacific region.